Evaluasi Kinerja Karyawan Operator Berbasis Pengembangan Sumber Daya Manusia, Kompensasi Dan Komitmen Organisasional - Ibnu Rahabistara, Wibi; Respati, Harianto (Sekolah Tinggi Ilmu Manajemen Indonesia (STIMI) Banjarmasin, 2017)
This study Aimed to describe the Human Resources Development, Compensation,Organizational Commitment and Employee Performance Operator PT. HM Sampoerna Tbk.Sukorejo Pandaan, analyze the influence of Human Resources Development, Compensation,and Organizational Commitment to Employee Performance Operator PT. HM SampoernaTbk. Sukorejo Pandaan, as well as identify and analyze between the variables of HumanResources Development, Compensation, and Organizational Commitment dominant influenceon employee performance Operator PT. HM Sampoerna Tbk. Sukorejo Pandaan. Thepopulation in this study were employees of the operator PT. HM. Sampoerna Tbk, SukorejoPandaan total 670 employees. The number of samples in this study were 250 respondents. Thesampling technique used in the study is simple random sampling assuming a homogeneouspopulation. The analysis technique used is multiple regression analysis, F test and t test. Theanalysis showed that the development of human resources, compensation and organizationalcommitment influence on the performance of employees of PT. HM. Sampoerna Tbk SukorejoPandaan, which means that the development of human resources properly implemented,supported with adequate compensation, and high organizational committed employees canimprove employee performance. Development of human resources more dominant influencethan compensation and organizational commitment to employee performance PT. HM.Sampoerna Tbk Sukorejo Pandaan. This suggests that the main thing to consider to improvethe performance of employees of PT. HM. Sampoerna Tbk Sukorejo Pandaan namely humanresource development.Keywords: human resource development, compensation, organizational commitmentaffects employee performance